Gender-based violence and child nutrition in fragile settings: exploring intersections and opportunities for evidence generation - Sarah R Meyer; Luissa Vahedi; Elisabeth Roesch; Christine Heckman; Silvia Bhatt Carreno; Andrew Beckingham; Megan Gayford; Manuela Orjuela-Grimm (BMJ Nutrition, Prevention & Health)
Gender-based violence (GBV) is disproportionately perpetrated against women and girls, due to harmful gender and social norms, structural gender-based power inequalities and pervasive discrimination against women and girls globally. In settings of fragility (eg, weak governance and humanitarian emergencies), risk factors for GBV are exacerbated while protective factors are eroded. Adequate nutrition is critical for mental and physical health and ensuring adequate nutrition for children in fragile settings is particularly critical. Fragile settings include heightened risk for GBV and malnutrition, but the combined impact of these two health contributors has rarely been examined together. Based on a rapid evidence assessment, we present evidence for associations between GBV against women and girls and child nutrition outcomes, identifying gaps in the evidence base and discussing key conceptual and methodological issues concerning research on this intersection. Improved understanding of the intersections between GBV and nutrition outcomes can help further highlight the linkages between these two public health issues and help inform programming and policy in both sectors.